Diverse Effects of Exosomes on COVID-19: A Perspective of Progress From Transmission to Therapeutic Developments - Gurunathan, Sangiliyandi; Kang, Min Hee; Kim, Jin-Hoi (Frontiers in Immunology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new strain of coronavirus and the causative agent of the current global pandemic of coronavirus disease 2019 (COVID-19). There are currently no FDA-approved antiviral drugs for COVID-19 and there is an urgent need to develop treatment strategies that can effectively suppress SARS-CoV-2 infection. Numerous approaches have been researched so far, with one of them being the emerging exosome-based therapies. Exosomes are nano-sized, lipid bilayer-enclosed structures, share structural similarities with viruses secreted from all types of cells, including those lining the respiratory tract. Importantly, the interplay between exosomes and viruses could be potentially exploited for antiviral drug and vaccine development. Exosomes are produced by virus-infected cells and play crucial roles in mediating communication between infected and uninfected cells. SARS-CoV-2 modulates the production and composition of exosomes, and can exploit exosome formation, secretion, and release pathways to promote infection, transmission, and intercellular spread. Exosomes have been exploited for therapeutic benefits in patients afflicted with various diseases including COVID-19. Furthermore, the administration of exosomes loaded with immunomodulatory cargo in combination with antiviral drugs represents a novel intervention for the treatment of diseases such as COVID-19. In particular, exosomes derived from mesenchymal stem cells (MSCs) are used as cell-free therapeutic agents. Mesenchymal stem cell derived exosomes reduces the cytokine storm and reverse the inhibition of host anti-viral defenses associated with COVID-19 and also enhances mitochondrial function repair lung injuries. We discuss the role of exosomes in relation to transmission, infection, diagnosis, treatment, therapeutics, drug delivery, and vaccines, and present some future perspectives regarding their use for combating COVID-19.